LDPC Code Design for Nonuniform Power-Line Channels. (26th June 2007) - Sanaei Sanaei, Ali Ali; Ardakani Ardakani, Masoud Masoud
Abstract : We investigate low-density parity-check code design for discrete multitone channels over power lines. Discrete multitone channels are well modeled as nonuniform channels, that is, different bits experience various channel parameters. We propose a coding system for discrete multitone channels that allows for using a single code over a nonuniform channel. The number of code parameters for the proposed system is much greater than the number of code parameters in conventional channel. Therefore, search-based optimization methods are impractical. We first formulate the problem of optimizing the rate of an irregular low-density parity-check code, with guaranteed convergence over a general nonuniform channel, as an iterative linear programming which is significantly more efficient than search-based methods. Then we use this technique for a typical power-line channel. The methodology of this paper is directly applicable to all decoding algorithms for which a density evolution analysis is possible.